Exploration of the Pucuak Rabuang Motif in Exotic Dramatic Fashion Design - Rezki Mutia Rahmi; Novina Yeni Fatrina; Mirda Aryadi; Fadri Rahmat (Kirana Publisher (KNPub), 2026)
The work entitled “Exotic Dramatic Style Inspired by the Pucuak Rabuang Motif” is based on the visual form and philosophical meaning of the pucuak rabuang motif, symbolizing growth and hope, which is developed into exotic dramatic fashion designs. The collection aims to introduce cultural values through unique, ethnic, and dramatic fashion. Three garment categories are produced: ready-to-wear, ready-to-wear deluxe, and haute couture, each complemented by headpiece accessories. Maroon and gold dominate the color palette, while satin jacquard, velvet, and Silungkang songket are used as the main materials. The creative process includes motif exploration, design development, and garment realization using couture sewing techniques, embroidery, and bead embellishment. The resulting collection is suitable for parties and fashion shows and will be presented through a fashion show at Hoeridjah Adam Hall, Institut Seni Indonesia (ISI) Padangpanjang, providing a professional venue to showcase the works. Keywords: Fashion, Exotic Dramatic, Pucuak Rabuang.